Inhibitory Effect of Sesamolin on Melanogenesis in B16F10 Cells Determined by In Vitro and Molecular Docking Analyses - Baek, Seung-Hwa; Kang, Myung-Gyun; Park, Daeui (Current Pharmaceutical Biotechnology, 2020)
Background: Melanin protects the skin against the harmful effects of ultraviolet irradiation. However, melanin overproduction can result in several aesthetic problems, including melasma, freckles, age spots and chloasma. Therefore, development of anti-melanogenic agents is important for the prevention of serious hyperpigmentation diseases. Sesamolin is a lignan compound isolated from sesame seeds with several beneficial properties, including potential for melanin inhibition. Objective: The aim of this study was to evaluate the anti-melanogenic effect of sesamolin in cell culture in vitro and the underlying mechanism of inhibition using molecular docking simulation. Methods: Melanogenesis was induced by 3-isobutyl-1-methylxanthine in B16F10 melanoma cells, and the inhibitory effects of sesamolin were evaluated using zymography, a tyrosinase inhibitory activity assay, western blotting, and real-time reverse transcription-polymerase chain reaction analysis. Docking simulations between sesamolin and tyrosinase were performed using Autodock vina. Results: Sesamolin significantly inhibited the expression of melanogenesis-related factors tyrosinase, and tyrosinase-related proteins 1 and 2 at the mRNA and protein levels. Treatment of melanoma cells with 50 μM sesamolin demonstrated the strongest inhibition against intercellular tyrosinase and melanin synthesis without exerting cytotoxic effects. Sesamolin significantly reduced mushroom tyrosinase activity in a dose-dependent manner via a competitive inhibition mechanism. Tyrosinase docking simulations supported that sesamolin (-6.5 kcal/mol) bound to the active site of tyrosinase more strongly than the positive control (arbutin, -5.7 kcal/mol). Conclusion: Sesamolin could be developed as a melanogenesis inhibiting agent owing to its dual function in blocking the generation of melanogenesis-related enzymes and inhibiting the enzymatic response of tyrosinase.
Keywords: melanogenesis-related protein